Aggression, predictability of the environment, and self-regulation: Reconciliation with animal research. (2017) - Tops, Mattie; van der Linden, Dimitri
Abstract: Apparently inconsistent with the CLASH model, animal research relates predictable environments to rigid routine behaviors and aggression. However, our work on evolutionary and neural adaptations to (un)predictable environments may be able to reconcile the CLASH model with the animal research, but also suggests complexities beyond the dichotomous approach of CLASH.